ØªÙ†Ù…ÙŠØ© Ø§Ù„ÙˆØ³ÙŠÙ„ØªÙ‰ Ø¬ÙˆØ¬Ù„ ÙÙˆØ±Ù… ÙÙŠ Ù…ÙˆØ§Ø¯ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø¹Ø§Ø´Ø± Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø´Ø§ÙØ¹ÙŠØ© Ø§Ù„Ø¹Ø²ÙŠØ²ÙŠØ© Ø§Ù„Ø«Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ù†Ø¯ÙˆÙ†Ø¬ - Heni Sulasani; Suparmanto Suparmanto (Lughatu Ad-Dhat, 2021)
This study aims to develop a Google Form media on Arabic subjects in the tenth class of the Shafi’i Azizia Thanawiya Islamic School Bandung because the Shafi’i Al-Aziziya Thanawiya Madrasa Bandung has sufficient potential but is not applied in learning, which makes learning monotonous which leads to students lacking enthusiasm and desire to try things new to learning. The media development research researchers in this Google Form used Borg and Gold's own research method as written in Seggiono's book on quantitative and qualitative research methods and research and development. Where in the book there are 10 steps of research but researchers only use 8, they are: potential and problems, information gathering, product design, design validation, design improvement, product testing, product review, and trial use. After executing the stages of the eight steps of the research and development method, the researcher obtained the search results as follows: Google products form media development in Arabic materials are suitable to be used after delving into the process of media expert and materials expert. For the media experts rating, they get 91.6% of the 12 items with an average value of 3.6, for the subject matter experts, they score 89.3% of the 14 statement items with an average value of 3.6, and student responses get a score of 90% out of the 10 statement items. Based on the study results, determine whether or not the students' scores increased after using the media, the researchers concluded Google Form because based on the validity of the 15-item test and 10 questions were valid because the score table is 0.444. Calculation of the bipartisan T-test correlation before and after the use of media was reported to influence student value because ha was accepted and he was rejected.